A RESEARCH ON STUDENTS' ATTITUDE TOWARDS MATHEMATICS - Vladislav, BIBA; SMETANOVÁ, Dana (Trends in education, 2015)
The paper describes the results of research among students of chemistry at Palacky University in Olomouc, whose attitude to mathematics was investigated by a questionnaire. We focused on connections between responses using statistical test of independence.
Keywords: mathematics; questionnaire research; statistics independence test.